PENGEMBANGAN JASA LINGKUNGAN DI HUTAN LINDUNG DALAM MENDUKUNG EKONOMI MASYARAKAT DAN PENDAPATAN DAERAH - Airansi, Adraisna; Doria, Cici; Wulandari, Christine; Bakri, Samsul; Asmara, Sandi (Universitas Pattimura, 2023)
Developing environmental services in protected forests can be done in various ways, such as developing natural tourism, planting trees to reduce carbon emissions, and managing water resources. The approach used in this study is qualitative with the desk research method. The development of environmental services in protected forests can be carried out through various approaches, such as community-based forest management, partnerships between government and the private sector, and the use of information and communication technology. The development of environmental services can increase people's income by increasing the economic value of products produced from protected forests, assisting in maintaining sustainable management of natural resources, and increasing the availability of natural resources that are beneficial for human life and the ecosystem. The main challenges in managing environmental services are lack of access to capital and technology, as well as lack of public awareness and participation in managing natural resources. There are opportunities for developing environmental services in protected forests, such as increasing public awareness of the importance of preserving protected forests and advances in information and communication technology that can be used in developing environmental services. The development of environmental services in protected forests through social forestry programs is a solution to maintain human survival and preserve protected forests. This program provides economic, social and technological benefits for local communities and encourages sustainable forest management, as well as increasing community awareness in preserving forest functions.